The house of mirth - Wagner-Martin, Linda (Twayne Publishers, 1990)
Provides in-depth analysis of the literary work The House of Mirth, as well as its importance and critical reception. Includes a chronology of the life and works of the author
Description based on print version record
Keywords: Wharton; Edith; House of mirth; Single women in literature